Empowerment Moderates Entrepreneurial Motivation and Samiler MSME Independence in Indonesia - Sri Vijayanti; Mubarokah Mubarokah; Ika Sari Tondang (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: MSMEs play an important role in Indonesia’s economy, yet business independence remains a central challenge for small enterprise sustainability. Specific Background: Samiler cracker business owners in the Kayangan Industrial Center face intense business competition, inactive producers, and continued dependence on assistance despite receiving empowerment programs. Knowledge Gap: Previous research has examined the direct relationship between entrepreneurial motivation and business independence, but has not sufficiently addressed the external role of community empowerment as a moderating variable in Samiler cracker MSMEs. Aims: This study aimed to analyze the relationship between entrepreneurial motivation and MSME independence and to examine community empowerment as a moderating variable among 31 active Samiler cracker business owners in Kayangan Village, Jombang. Results: SEM PLS analysis using SmartPLS 4.0 showed that entrepreneurial motivation had a positive and significant relationship with MSME independence, with a path coefficient of 0.643, T statistic of 6.207, and P value of 0.000. Community empowerment moderated the relationship between entrepreneurial motivation and MSME independence, with a path coefficient of 0.317, T statistic of 2.603, and P value of 0.009. The R square value of 0.720 indicated that 72% of MSME independence was explained by the research model. Novelty: This study positions community empowerment as a moderating mechanism in the entrepreneurial motivation and MSME independence model. Implications: Empowerment programs can be evaluated and improved to support more independent Samiler MSME management. Highlights: The structural model explained 72% of business autonomy. Motivation showed a positive significant path coefficient. Community programs strengthened the tested moderation pathway. Keyword: Businessmen, Community Empowerment, Entrepreneurial Motivation, MSME Independence, Samiler Crackers Industrial Center